2017
DOI: 10.1158/2159-8290.cd-17-0698
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Activation and Blood–Brain Barrier Disruption in Neurotoxicity after Adoptive Immunotherapy with CD19 CAR-T Cells

Abstract: Lymphodepletion chemotherapy followed by infusion of CD19-targeted chimeric antigen receptor (CAR)-modified T (CAR-T) cells can be complicated by neurologic adverse events (AEs) in patients with refractory B cell malignancies. In 133 adults treated with CD19 CAR-T cells we found that acute lymphoblastic leukemia, high CD19+ cells in bone marrow, high CAR-T cell dose, cytokine release syndrome, and preexisting neurologic comorbidities were associated with increased risk of neurologic AEs. Patients with severe n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
1,409
15
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,020 publications
(1,547 citation statements)
references
References 24 publications
(45 reference statements)
48
1,409
15
12
Order By: Relevance
“…An association has been noted between higher CRS and neurotoxicity grades and serum Von Willebrand Factor (VWF), suggesting greater endothelial activation in both CRS and CRES and this was corroborated with higher levels of Angiopoietin-2 (Ang-2) 38,45 . Importantly, this work also demonstrated that pre-existing endothelial activation (prior to CAR T cell infusion, as determined by increased VWF and Ang-2:Ang-1 ratios), may be associated with increased subsequent CRS severity.…”
Section: Car T Cell-related Encephalopathy Syndrome (Cres)mentioning
confidence: 89%
See 3 more Smart Citations
“…An association has been noted between higher CRS and neurotoxicity grades and serum Von Willebrand Factor (VWF), suggesting greater endothelial activation in both CRS and CRES and this was corroborated with higher levels of Angiopoietin-2 (Ang-2) 38,45 . Importantly, this work also demonstrated that pre-existing endothelial activation (prior to CAR T cell infusion, as determined by increased VWF and Ang-2:Ang-1 ratios), may be associated with increased subsequent CRS severity.…”
Section: Car T Cell-related Encephalopathy Syndrome (Cres)mentioning
confidence: 89%
“…Investigation of biomarkers of severe CRS in a predominantly paediatric cohort revealed an association between low fibrinogen and grade 4 CRS in paediatric patients 35 . This was explored further in an adult cohort treated at the Fred Hutchinson Cancer Center 38,45 where grade 4 or greater CRS was associated with hypofibrinogenaemia, increased d-dimers and reduced platelets, consistent with disseminated intravascular coagulation.…”
Section: Cytokine Release Syndrome (Crs)mentioning
confidence: 99%
See 2 more Smart Citations
“…[139][140][141] Initial studies often used cyclophosphamide alone for lymphodepletion, but enhanced expansion and persistence has been documented when cyclophosphamide is combined with other agents, most commonly including fludarabine. Although there has been some concern that fludarabine may have increased the risk for neurotoxicity (given its known association with neurologic events at very high doses), which is observed after CAR-T therapy (discussed in "CRES"), the predominance of the data argues against this association being causative, 142,143 and cyclophosphamide/ fludarabine chemotherapeutic regimens are widely used with both CD19-directed and other CAR-T therapies. The goal of preinfusion chemotherapy is twofold: (1) to deplete endogenous T cells that might increase the risk of T-mediated rejection of CAR-T cells, 144 and (2) to enhance CAR-T expansion in the lymphodepleted host.…”
Section: Preinfusion Chemotherapymentioning
confidence: 99%